When Push Comes to Shove—The Moral Fiction of Reason-Based Situational Control and the Embodied Nature of Judgment - Bergmann, Lasse T.; Wagner, Jennifer (Frontiers in Psychology, 2020)
It is a common socio-moral practice to appeal to reasons as a guiding force for one’s actions. However, it is an intriguing possibility that this practice is based on fiction: reasons cannot or do not motivate the majority of actions—especially moral ones. Rather, pre-reflective evaluative processes are likely responsible for moral actions. Such a view faces two major challenges: i.) pre-reflective judgements are commonly thought of as inflexible in nature, and thus they cannot be the cause of the varied judgements people rely on in everyday life, and ii.) if reflective reason-based judgements do not play a strong causative role in judgement, why do people rely on the articulation of reasons in their moral practices? We argue that the pre-reflective judgements motivating moral actions are embodied in nature. The experience of the rightness of an action that drives a person to act depends on the sensorimotor interactions that have cultivated an agent’s perspective on the world. These interactions are embedded in relational contexts, relative to which judgements are individuated. Because of this relational embeddedness they are more flexible than they are commonly thought to be, enabling us to explain the variety of human behavior by appealing to them. The Anglo-European practice of appealing to reason as if they were propositional belief-statements motivating actions can be accounted for as nothing more than an idiosyncratic way of constructing narratives to clarify and express the relational context of intentional actions.